Molecular Characteristics and Epidemiological Significance of Shiga Toxin-Producing Escherichia coli O26 Strains - Zhang, Wen-Lan (American Society for Microbiology, 2000)
Fifty-five Shiga toxin (Stx)-producing Escherichia coli (STEC) O26:H11 and O26:H(−) strains isolated from humans between 1965 and 1999 in Germany and the Czech Republic were investigated for their chromosomal and plasmid characteristics. All motile (n = 23) and nonmotile (n = 32) STEC O26 strains were shown to possess the identical flagellin subunit-encoding gene (fliC). We observed a striking recent shift of the stx genotype from stx(1) to stx(2) among the STEC O26 isolates. While stx(1) was the exclusive genotype identified in our collection until 1994, 94% of the isolates obtained after 1997 possessed stx(2) either alone (71%) or together with stx(1) (23%). Plasmid profiling demonstrated a remarkable heterogeneity with respect to plasmid sizes and combinations. Southern blot analysis of plasmid DNA with probes specific to potential accessory virulence genes revealed considerable additional variability in gene composition and arrangement. Pulsed-field gel electrophoresis (PFGE) differentiated 16 subgroups among the 55 STEC O26 strains. Using these techniques we demonstrate the emergence of a new clonal subgroup characterized by PFGE pattern A and a unique combination of virulence markers including stx(2) and a single, approximately 90-kb plasmid harboring the enterhemorrhagic E. coli hlyA and etp genes. The proportion of PFGE subgroup A strains among STEC O26 isolates rose from 30% in 1996 to more than 50% in 1999. Four clusters of infections with the clonal subgroup A were identified. We conclude that the STEC serogroup O26 is diverse and that pathogenic clonal subgroups can rapidly emerge during short intervals. The extensive genetic diversity of STEC O26 provides a basis for molecular subtyping of this important non-O157 STEC serogroup.